2008
DOI: 10.1002/adma.200702930
|View full text |Cite
|
Sign up to set email alerts
|

Universal Block Copolymer Lithography for Metals, Semiconductors, Ceramics, and Polymers

Abstract: A universal block copolymer lithography is developed for a broad spectrum of materials including metals, semiconductors, ceramics, and polymers by combining advanced film deposition techniques with block copolymer lithography. The figure presents a nanopatterned platinum film prepared by applying universal block copolymer lithography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
112
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 33 publications
1
112
0
Order By: Relevance
“…These requirements are extremely challenging for self-assembly and lithography alike and include sub-nm line edge roughness and sub-4 nm positioning (of a feature expressed from the overlay registry requirements) accuracy for the 16 nm technology node. The potential application of BCPs in this area has been extensively reported and reviewed (Jeong et al, 2008). These reviews also detail the methods by which the polymer nanopatterns can be processed into active components (i.e., nanowires, nanodots of semiconducting, magnetic or conducting materials).…”
Section: The Need For Low Defect Concentrations In Self-assembled Sysmentioning
confidence: 99%
“…These requirements are extremely challenging for self-assembly and lithography alike and include sub-nm line edge roughness and sub-4 nm positioning (of a feature expressed from the overlay registry requirements) accuracy for the 16 nm technology node. The potential application of BCPs in this area has been extensively reported and reviewed (Jeong et al, 2008). These reviews also detail the methods by which the polymer nanopatterns can be processed into active components (i.e., nanowires, nanodots of semiconducting, magnetic or conducting materials).…”
Section: The Need For Low Defect Concentrations In Self-assembled Sysmentioning
confidence: 99%
“…Arrays of metallic and dielectric nanodots and nanowires have been fabricated using these selfassembled polymeric templates and opportunities clearly exist for a very large variety of material choices (Farrell et al 2010;Castro et al 2013;Jeong et al 2008;Hong et al 2010;Xiao et al 2005). So far, limited research activity is documented in the literature on the growth of Si and Ge crystalline nanostructures using block copolymer templates (Farrell et al 2010;Castro et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a pioneering work, Guarini et al demonstrated the feasibility of the metal lift-off process using block copolymers (Guarini et al 2003). Afterward several authors reported the possibility to fabricate high-density metal nanodots using similar procedures (Jeong et al 2008;Hong et al 2010;Xiao et al 2005). Similarly, many authors explored the possibility to form amorphous SiO 2 nanodots using block copolymer thin films as a template (Park et al 2008;Xu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled thin films of BCPs provide periodic arrays of nanoscale spheres, cylinders, lamellae with ultrafine tunability of feature size (3-50 nm) and arbitrary large area scalability. After pattern transfer, organic BCP film can be easily disposed by a mild etching process, which is highly compatible with traditional photoresist based semiconductor processing [1][2][3][4].To date, various DSA technologies have been exploited for the well-ordered device-oriented nanopatterns. In general, DSA approaches synergistically integrate the bottom-up process of BCP self-assembly with a top-down process of conventional photolithography, such as ArF lithography, I-line lithography or Ebeam lithography.…”
mentioning
confidence: 99%
“…Self-assembled thin films of BCPs provide periodic arrays of nanoscale spheres, cylinders, lamellae with ultrafine tunability of feature size (3-50 nm) and arbitrary large area scalability. After pattern transfer, organic BCP film can be easily disposed by a mild etching process, which is highly compatible with traditional photoresist based semiconductor processing [1][2][3][4].…”
mentioning
confidence: 99%